(untitled) (Praxis Educativa, 2022)
This article describes economics classes in secondary schools in Argentina during the health emergency by COVID-19. The situation of off- site classes meant that the schools continued to function, ensuring the pedagogical continuity of their students, but resulting in changes in school life that impacted the configurations of the classes. For data collection, a self-administered online survey form and semi-structured interviews conducted by video call were conducted. The results show three large class configurations according to the spaces, times, frequency, and media used. The first group is characterized by an attempt to emulate on-site classes. A second group presents traits where the class appears differentiated, customizing in the spaces, times, frequencies, and media used. A third group is identified with classes in asynchronous times, with diffuse or not delimitated class places.